IoT as a Business Performance Support: A Bibliometric Study - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study examines the development of research on the Internet of Things as a support for business performance through a bibliometric approach. Using data retrieved from the Scopus, the study analyzes publication trends, influential sources, and the intellectual structure of the field. The analysis is conducted using VOSviewer and Bibliometrix to map co-authorship, co-citation, and keyword co-occurrence networks. The findings reveal that IoT research has evolved from a primary focus on technological infrastructure, such as security and connectivity, toward more integrated themes including data analytics, artificial intelligence, and industry applications. Several key clusters emerge, highlighting the role of IoT in operational efficiency, business process transformation, and intelligent decision-making. The results also indicate a growing convergence between IoT and advanced digital technologies, suggesting a shift toward more strategic and performance-oriented applications. This study contributes by positioning IoT as a capability that supports business performance and by identifying emerging research directions for future investigation.